2005
DOI: 10.1038/sj.ijir.3901426
|View full text |Cite
|
Sign up to set email alerts
|

Why do patients with heart failure suffer from erectile dysfunction? A critical review and suggestions on how to approach this problem

Abstract: Chronic heart failure (HF) is an increasingly common cardiovascular disorder. The goal of healthcare providers is to optimize quality of life in this population, including sexual health. Up to 75% of patients with HF report erectile dysfunction (ED). As HF is a condition with distinct physiologic sequelae, some unique organic and psychological factors contributing to ED in this patient population have been identified, along with risk factors common to the development of coronary artery disease, HF and ED. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 137 publications
0
47
1
1
Order By: Relevance
“…Consequently, before scoring ED severity, patients with hypertension should receive no medication with thiazide diuretics, central-acting sympatholytic agents, or b-blockers, even though the role of these agents in worsening ED is still controversial. 36 Besides, as the study population consists of men at a urologic clinic, there is a referral bias that might limit the overall generation of data presented. On the contrary, thinking about it in another way, this is the value of this manuscript for its being near to the real clinical practice world.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, before scoring ED severity, patients with hypertension should receive no medication with thiazide diuretics, central-acting sympatholytic agents, or b-blockers, even though the role of these agents in worsening ED is still controversial. 36 Besides, as the study population consists of men at a urologic clinic, there is a referral bias that might limit the overall generation of data presented. On the contrary, thinking about it in another way, this is the value of this manuscript for its being near to the real clinical practice world.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial function has been shown to be altered in patients with HF (ischemic or nonischemic in nature), diabetes mellitus and CAD. 60 Some animal studies showed beneficial effects of PDE-5i use on the endothelium function in diabetics. For example, Ahn et al 61 studied the effect of DA-8159 (PDE-5i) on diabetic rats and demonstrated that chronic administration of PDE-5i attenuated the development of ED.…”
Section: Effect On the Endotheliummentioning
confidence: 99%
“…7,8 ED is associated with coronary artery disease, 9 hypertension 10 and now heart failure (HF). 11 The goal of this review is to describe the prevalence of ED in HF patients, causes of ED specific to patients with HF, the cardiac risk assessment of sexual activity, the safety of PDE-5 inhibitors to treat ED in HF patients, the efficacy of PDE-5 inhibitors for ED in HF patients, the hemodynamic effects of PDE-5 inhibitors on HF, the potential mechanisms by which PDE-5 inhibitors improve HF and role of PDE-5 inhibitors in pulmonary hypertension.…”
Section: Introductionmentioning
confidence: 99%